2005
DOI: 10.1007/s10531-004-5055-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological quality of running waters in protected areas: the influence of size and land use

Abstract: There are still substantial questions about whether protected areas affect the quality and biodiversity of surface waters within their borders. In this study, the size and land use of 19 protected areas of Latium Region (central Italy) were related to the biological quality of 32 streams running inside them. Additionally, the biological quality of 18 out of the 32 streams was compared with the quality recorded on the same streams outside the boundaries of the protected areas. The biological quality was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 71 publications
1
15
0
4
Order By: Relevance
“…Variance partitioning with partial CCA indicated that benthic invertebrate assemblages were predominantly influenced by local land-use (as expressed by the Anthropogenic Index), channel morphology and water quality, each explaining a significant proportion of variance. Previous surveys support the role of local land-use and morphological features in structuring benthic assemblages in this Region [37], [38], [70].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Variance partitioning with partial CCA indicated that benthic invertebrate assemblages were predominantly influenced by local land-use (as expressed by the Anthropogenic Index), channel morphology and water quality, each explaining a significant proportion of variance. Previous surveys support the role of local land-use and morphological features in structuring benthic assemblages in this Region [37], [38], [70].…”
Section: Discussionsupporting
confidence: 55%
“…The following k values were attributed to the respective CORINE land use categories: 1, natural woods; 2, pastures, meadows, bush areas, scrub and olive grove; 3 agricultural areas and urban green areas; 4, urban and industrial areas. The 1 km buffer was chosen since, in this region, macroinvertebrates appeared influenced by land use at this scale [37], [38]. The index therefore represents a surrogate of anthropogenic development and ranges from 1 (minimum development) to 4 (maximum development).…”
Section: Methodsmentioning
confidence: 99%
“…In central Italy, many rivers are characterised by marked longitudinal patterns in anthropogenic pressure, with up-and middle-stream sections draining semi-natural or extensive agricultural areas, while downstream sections being detrimentally stressed by urbanisation, impoundment and industrial sewage effluents (Solimini et al, 2001;Mancini et al, 2005;Manfrin et al, 2013). In these circumstances, the extent to which benthic assemblages reflect differences among local micro-habitat types or larger-scale longitudinal variation is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively good overlap between streams with high species richness and the protected natural spaces shows the importance of these areas as a starting point for monitoring and conservation plans of the aquatic biocoenosis of the lower Guadiana River basin (Iba´n˜ez et al, 1997;European Parliament and Council Directive 2000/60/EC;So´lymos and Fehe´r, 2005). It is also important to preserve streams as biological corridors within protected areas, creating buffer zones between a larger number of different habitats and, consequently, a richer freshwater biodiversity (Lammert and Allan, 1999;Voelz and McArthur, 2000;Haila, 2002;Sa´nchez-Ferna´ndez et al, 2004;Bonn and Gaston, 2005;Mancini et al, 2005). Nevertheless, some important streams with high species richness and the presence of naiads (Unionidae) } Foupana (GD81), Odeleite (GD88), Chanza (GD67) and, partially, Ardila (GD49) and Oeiras (GD60) } remain unprotected and threatened by tourism and pollution.…”
Section: Conservation Considerationsmentioning
confidence: 99%